A developmental perspective on mind wandering and its relation to goal-directed thought - Pavlova, Maria (Universität Vechta, 2025)
Mind wandering (i.e., thoughts drifting from one topic to another, with no immediate connection to the perceptual field or the ongoing task) is a widespread cognitive phenomenon. There has been increasing research interest in mind wandering in children and adolescents. However, the developmental origins of this phenomenon remain largely unknown. In the present article, I summarize the purported cognitive mechanisms of mind wandering in adults and review the empirical findings on mind wandering and automatic memory retrieval in children and adolescents. I propose a comprehensive account of the emergence of mind wandering in early and middle childhood, covering the development of its central components identified in the adult literature: motivational and emotional processes, episodic and semantic processes, perceptual decoupling, and meta-awareness. Paying special attention to the roles of developing motivation and executive control, I then address the relationship between mind wandering and goal-directed thought in children.
Keywords: Attention development; Direct memory retrieval; Executive control development; Motivated attention; Spontaneous thought; Stiumulus-independent thought; Task-unrelated thought; Philosophie und Psychologie::150 Psychologie